2020
DOI: 10.18632/aging.103623
|View full text |Cite
|
Sign up to set email alerts
|

Fully bayesian longitudinal unsupervised learning for the assessment and visualization of AD heterogeneity and progression

Abstract: Tau pathology and brain atrophy are the closest correlate of cognitive decline in Alzheimer’s disease (AD). Understanding heterogeneity and longitudinal progression of atrophy during the disease course will play a key role in understanding AD pathogenesis. We propose a framework for longitudinal clustering that simultaneously: 1) incorporates whole brain data, 2) leverages unequal visits per individual, 3) compares clusters with a control group, 4) allows for study confounding effects, 5) provides cluster visu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…Sub1 (278 MCI & 85 AD) and Sub4 (164 MCI & 34 AD) have the highest proportion of MCI. The normal anatomy subtype has been confirmed in previous works (Dong et al, 2016b; Ezzati et al, 2020; Jung et al, 2016; Nettiksimmons et al, 2014; Ota et al, 2016; Poulakis et al, 2020, 2018; Ten Kate et al, 2018; Yang et al, 2020). In (Dong et al, 2016b), the authors examined the external validation of the subtypes.…”
Section: Discussionsupporting
confidence: 77%
“…Sub1 (278 MCI & 85 AD) and Sub4 (164 MCI & 34 AD) have the highest proportion of MCI. The normal anatomy subtype has been confirmed in previous works (Dong et al, 2016b; Ezzati et al, 2020; Jung et al, 2016; Nettiksimmons et al, 2014; Ota et al, 2016; Poulakis et al, 2020, 2018; Ten Kate et al, 2018; Yang et al, 2020). In (Dong et al, 2016b), the authors examined the external validation of the subtypes.…”
Section: Discussionsupporting
confidence: 77%
“…Ferreira et al and follow-up studies from our lab used visual rating scales of brain atrophy in medial temporal, frontal and posterior cortices ( Ferreira et al , 2017 , 2018 , 2019 ; Persson et al , 2017 ; Ekman et al , 2018 ; Oppedal et al , 2019 ; Machado et al , 2020 ) and determined clinical cut points for abnormality ( Ferreira et al , 2015 ). We also used unsupervised clustering in another cross-sectional study by Poulakis et al (2018) , which was recently extended for subtyping on longitudinal data ( Poulakis et al , 2020 ). Other groups used different unsupervised clustering methods ( Noh et al , 2014 ; Dong et al 2015, 2017 ; Hwang et al 2016 ; Na et al , 2016 ; Zhang et al 2016 ; Park et al 2017 ; Varol et al 2017 ), highlighting the methodological variability across studies.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, no head-to-head comparison of subtyping methods has been published so far. Such a comparison arises as an urgent and important step towards facilitating consistent progress in this field, especially with the current surge in subtyping studies using sMRI investigating subtype or disease progression ( Young et al , 2018 ; Marinescu et al , 2019 ; Poulakis et al , 2020 ) and tau PET ( Whitwell et al , 2018 ; Charil et al , 2019 ; Jeon et al , 2019 ). To illustrate this problem, in the present study, we applied different subtyping methods reported in five previous studies ( Murray et al , 2011 ; Byun et al , 2015 ; Ferreira et al , 2017 ; Risacher et al , 2017 ; Poulakis et al , 2018 ; Charil et al , 2019 ) on sMRI and tau PET data from the same cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from our lab used visual rating scales of brain atrophy in medial temporal, frontal, and posterior cortices (713), and determined abnormality based on clinical cut points (14). We also used an unsupervised clustering method in another cross-sectional study (15), which has recently been extended for subtyping on longitudinal data (16). Other groups used different unsupervised clustering methods (1724), highlighting the methodological variability across studies.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, no head-to-head comparison of subtyping methods has been published so far. Such a comparison arises as an urgent and important step towards facilitating consistent progress in this field, especially with the current surge in subtyping studies using longitudinal sMRI (16,26,27) and tau PET (3,25,28). To illustrate this problem and substantiate our claim for harmonizing subtyping methods, we applied subtyping methods based on five previous studies (1,5–7,15,25), on sMRI and tau PET data, in the same cohort.…”
Section: Introductionmentioning
confidence: 99%